The Impact of Globalization on Welfare and Gender Equality in Indonesia - Maichal, Maichal; Wijaya, Justin; Putra, Sinar Dharmayana (Jurnal Ekonomi Kuantitatif Terapan; 2023: Vol. 16, No. 2, Agustus 2023 (pp.187-360)DO - 10.24843/JEKT.2023.v16.i02.p04, 2023)
In recent years, there has been a growing debate about the future of globalization, with some calling for a reevaluation of its principles and practices. Issues such as income inequality, people’s welfare, and the impact on local communities have prompted discussions on how to make globalization more inclusive, sustainable, and equitable. In this study, there are three topics that will be discussed. First, this study will analyze the impact of economic globalization measured by foreign direct investment on people’s welfare and gender equality. Second, this study will analyze the impact of social globalization measured by the proportion of individuals with mobile phones and the number of foreign guests at star-rated hotels on people’s welfare and gender equality. Third, this study will analyze the impact of gender equality on people's welfare. This research used data from 34 provinces in Indonesia for the period of 2015-2021, which was sourced from the Central Bureau of Statistics. The data analysis methods employed in this research are Panel Least Squares and Panel Cross-Section Random Effects. This research discovered both positive and negative impacts of globalization. On the positive side, social globalization manifested through increased mobile phone ownership, exhibited a beneficial impact on the human development index, life expectancy, and gender equality. Gender equality also has a positive impact on human development index and life expectancy. On the negative side, foreign direct investment has failed to yield a positive impact on welfare. Furthermore, the presence of foreign tourists staying in star-rated hotels has a negative impact on life expectancy and gender equality.